2011
DOI: 10.1289/ehp.1103729
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Exposure Estimation and Predicted versus Observed Serum Perfluorooctanoic Acid Concentrations for Participants in the C8 Health Project

Abstract: Background: People living or working in eastern Ohio and western West Virginia have been exposed to perfluorooctanoic acid (PFOA) released by DuPont Washington Works facilities.Objectives: Our objective was to estimate historical PFOA exposures and serum concentrations experienced by 45,276 non-occupationally exposed participants in the C8 Health Project who consented to share their residential histories and a 2005–2006 serum PFOA measurement.Methods: We estimated annual PFOA exposure rates for each individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
135
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(143 citation statements)
references
References 32 publications
3
135
0
Order By: Relevance
“…retrospective serum PFOa concentration estimates were from a multistage modeling procedure described in detail elsewhere 23,25,26 and briefly summarized here. Yearly air and drinking water PFOa concentrations were estimated using an environmental fate and transport model.…”
Section: Retrospective Serum Pfoa Concentration Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…retrospective serum PFOa concentration estimates were from a multistage modeling procedure described in detail elsewhere 23,25,26 and briefly summarized here. Yearly air and drinking water PFOa concentrations were estimated using an environmental fate and transport model.…”
Section: Retrospective Serum Pfoa Concentration Estimatesmentioning
confidence: 99%
“…Yearly intake rates were used in an absorption/distribution/metabolism/excretion model to generate yearly serum PFOa concentration estimates. 26 For plant workers, an occupational exposure model (using work history information along with modeled job-and departmentspecific serum concentration estimates) was used to generate yearly serum PFOa concentration estimates for years when they worked at the plant. 27 For years after workers stopped working at the plant, serum estimates were decayed at an annual rate of 18% until reaching the community exposure model estimates.…”
Section: Retrospective Serum Pfoa Concentration Estimatesmentioning
confidence: 99%
“…We estimated PFOA serum levels over time for these workers by considering occupational5 and residential exposures (the latter from contaminated drinking water) 6. In the mortality study, we found positive dose–response trends for kidney cancer and kidney disease, based on small numbers of deaths 16…”
Section: Introductionmentioning
confidence: 96%
“…Human exposure to PFOA can occur through occupational exposure5 or through food (contamination during preparation and from packaging), drinking water,6 house dust7 and air 8. PFOA was found in the serum of more than 99% of the general USA population in the 2005–2006 National Health and Nutrition Examination Survey (NHANES), with a median concentration of 4 ng/mL 9.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to environmental contaminants is often evaluated using tools known as biomarkers of exposure [1,2]. The urinary 1-hydroxypyrene (1-OHPyr) is a reliable and sensitive biomarker of exposure to the low-level occupational and environmental exposure to polycyclic aromatic hydrocarbons (PAHs).…”
Section: Introductionmentioning
confidence: 99%